Notes on the Union of Weakly Primary Submodules. (28th December 2011) - Ghiasvand Ghiasvand, Peyman Peyman; Farzalipour Farzalipour, Farkhonde Farkhonde
Abstract : Let R be a commutative ring with identity, and let M be an R -module. A proper submodule N of M is said to be weakly primary if 0 ≠ r m ∈ N for r ∈ R and m ∈ M, which implies that either m ∈ N or r n M ⊆ N for some positive integer n . In this paper, we study weakly primary submodules, and we investigate the union of weakly primary submodules of R -modules.